Meningkatkan Aktivitas dan Hasil Belajar Siswa Menggunakan Model PBL, TPS, dan Make a Match pada Siswa Kelas IV Sekolah Dasar - Tiana; Tika Puspita Widya Rini (Lembaga Pengembangan Kinerja Dosen, 2023)
The issue in this review is that low learning activity has an impact on low student learning results in class IV SDN Teluk Dalam 11. Through the Problem Based Learning Model, Think Pair Share, and Make A Match which is the best solution. The study aims to determine teacher activity, and to improve student learning results. This review utilized a subjective methodology with the sort of Homeroom Activity Exploration (Vehicle), which was completed in four gatherings. The subjects of the review were 4th grade understudies at SDN Teluk Dalam 11 Banjarmasin for the scholarly year 2022/2023, with a sum of 7 understudies. In this study, the data analysis used descriptive analysis techniques described from tables, graphs, and interpretations with percentages. The results of this study show that teacher activities at meeting I get a score of 20, meeting II get a score of 25, meeting II get a score of 26, and meeting IV get a score of 28. Student activities at meeting I get a percentage of 71.00%, meeting II get a percentage of 86.00%, meeting III and IV get a percentage of 100%. Student learning results at meeting II reached 86.00% and at meeting IV reached 100% (old style).